A Chiron approach towards the stereoselective synthesis of polyfluorinated carbohydrates. Issue 1 (December 2018) - Denavit, Vincent; Lainé, Danny; St-Gelais, Jacob; Johnson, Paul; Giguère, Denis
Abstract The replacement of hydroxyl groups by fluorine atoms on hexopyranose scaffolds may allow access to the discovery of new chemical entities possessing unique physical, chemical and ultimately even biological properties. The prospect of significant effects generated by such multiple and controlled substitutions encouraged us to develop diverse synthetic routes towards the stereoselective synthesis of polyfluorinated hexopyranoses, six of which are unprecedented. Hence, we report the synthesis of heavily fluorinated galactose, glucose, mannose, talose, allose, fucose, and galacturonic acid methyl ester using a Chiron approach from inexpensive levoglucosan. Structural analysis of single-crystal X-ray diffractions and NMR studies confirm the conservation of favored4 C 1 conformation for fluorinated carbohydrate analogs, while a slightly distorted conformation due to repulsive 1, 3-diaxial F···F interaction is observed for the trifluorinated talose derivative. Finally, the relative stereochemistry of multi-vicinal fluorine atoms has a strong effect on the lipophilicities (logP ). Polyfluorinated hexopyranoses display unique physical, chemical and biological properties, however their stereoselective synthesis is highly challenging. Here, the authors report a synthetic approach based on the chemical manipulation of inexpensive levoglucosan to obtain heavily fluorinated monosaccharides stereoselectively.